Analysing the influence of usability on user satisfaction in educational board game / Norraeffa Md Taib … [et al.] - Md Taib, Norraeffa; Abu Yazid, Zarinah; Osman, Idris; Daud, Shahreena; Othman, Mohd Zailani (2023)
Conventional instructional approaches exhibit limitations in their capacity to facilitate impactful learning results and user satisfaction. Consequently, educational board game (EBG) emerges as a dynamic solution, delivering an interactive and captivating learning journey. The purpose of this study is to analyse the impact of usability components on user satisfaction in EBG using the MEEGA+. This study adopted the non-probability of the purposive sampling technique to select participants from bachelor’s degree students enrolled in Personal Financial Planning (PFP) subject. A quantitative study was conducted using a self-administered questionnaire distributed, and the hypothesized relationships were assessed using Statistical Package for the Social Science (SPSS) version 29.0. The findings reported that usability components (aesthetics, learnability and operability) had significantly influenced user satisfaction in EBG for PFP subject. This study investigated the impact of usability components (aesthetics, learnability and operability) on user satisfaction which involved sample from bachelor’s degree students enrolled in PFP subject. Insights from MEEGA+, the results were restricted to students enrolled in particular subject and institution in EBG. This study motivates players to improve understanding on PFP subject concept and satisfaction in EBG. Educators may create a game-based learning to maximise learning and include into curriculum. This expands previous studies on the importance of usability components by adopting MEEGA+ which has consequences to educators and researchers. The theoretical framework allows academicians to investigate social learning process through EBG in game theory, cognitive and pedagogical approach.